HSP70 Expression in Nasal Epithelial Cells in Patients with Chronic Rhinosinusitis with Nasal Polyps - Onishchenko, Anatolii I.; Tkachenko, Anton S.; Kharchenko, Elina O.; Sklyaruk, Diana O. (Problems of Cryobiology and Cryomedicine, 2019)
Probl Cryobiol Cryomed 2019; 29(2): 166.